Protein kinases MpkA and SepH transduce crosstalk between CWI and SIN pathways to activate protective hyphal septation under echinocandin cell wall stress - Alexander G. Doan; Jessica E. Schafer; Casey M. Douglas; Matthew S. Quintanilla; Meredith E. Morse; Harley Edwards; Walker D. Huso; Kelsey J. Gray; JungHun Lee; Joshua K. Dayie; Steven D. Harris; Mark R. Marten (mSphere, 2025)
ABSTRACT This study investigates a previously unreported stress signal transduced as crosstalk between the cell wall integrity (CWI) pathway and the septation initiation network (SIN). Echinocandins, which target cell wall synthesis, are widely used to treat mycoses. Their efficacy, however, is species specific. Our findings suggest that this is due largely to CWI–SIN crosstalk and the ability of filamentous species to fortify with septa in response to echinocandin stress. To better understand this crosstalk, we used a microscopy-based assay to measure septum density, aiming to understand the septation response to cell wall stress. The echinocandin micafungin, an inhibitor of β-(1,3)-glucan synthase, was employed to induce this stress. We observed a strong positive correlation between micafungin treatment and septum density in wild-type strains. This finding suggests that CWI activates SIN under cell wall stress, increasing septum density to protect against cell wall failure. More detailed investigations, with targeted knockouts of CWI and SIN signaling proteins, enabled us to identify crosstalk occurring between the CWI kinase, MpkA, and the SIN kinase, SepH. This discovery of the previously unknown crosstalk between the CWI and SIN pathways not only reshapes our understanding of fungal stress responses, but also unveils a promising new target pathway for the development of novel antifungal strategies.IMPORTANCEEchinocandin-resistant species pose a major challenge in clinical mycology by rendering one of only four lines of treatment, notably one of the two that are well-tolerated, ineffective in treating systemic mycoses of these species. Previous studies have demonstrated that echinocandins fail against highly polarized fungi because they target only apical septal compartments. It is known that many filamentous species respond to cell wall stress with hyperseptation. In this work, we show that echinocandin resistance hinges on this dynamic response, rather than on innate septation alone. We also describe, for the first time, the signaling pathway used to deploy the hyperseptation response. By disabling this pathway, we were able to render mycelia susceptible to echinocandin stress. This work enhances our microbiological understanding of filamentous fungi and introduces a potential target to overcome echinocandin-resistant species.